Cardiovascular risk in patients with rheumatoid arthritis: the role of cholesterylester transfer protein - Taghreed F Mohammed Mostafa; Ali M Mursi; Sherry K Abdelrahman; Emad M Elshebiny; Sahar H Quashwa; Lobna Y Ebrahim (Journal of Medicine in Scientific Research, 2019)
Aim To detect serum level of cholesterylester transfer protein (CETP) (the enzyme involved in reverse cholesterol transport) in patients with rheumatoid arthritis (RA) and to evaluate its relation to various clinical parameters of the disease, lipid profile, and carotid intima-media thickness (CIMT) as a marker of atherosclerosis and cardiovascular disease risk. Patients and methods This study involved a total of 80 participants, comprising 50 patients with RA and 30 age-matched and sex-matched healthy controls. Detailed medical history and thorough clinical examination (general and musculoskeletal) as well as laboratory investigations including lipid profile were performed for all patients with RA. Serum level of CETP was assessed by enzyme-linked immunosorbent assay technique. Carotid ultrasound scan was performed for all patients with RA to detect CIMT. Results Serum level of CETP was significantly lower in patients with RA than controls (4.11 ± 2.77 ng/ml in patients with RA and 5.30 ± 2.73 ng/ml in controls, P = 0.003). Regarding lipid profile values, high-density lipoprotein was lower in patients with RA relative to controls (63.02 ± 12.8 vs. 69.8 ± 6.7 mg/dl, P = 0.012), whereas total cholesterol (218.9 ± 39.5 vs. 206.9 ± 31.8 mg/dl, P = 0.073), triglycerides (144.2 ± 16.2 vs. 136.1 ± 16.6 mg/dl, P = 0.059), and low-density lipoprotein (118.5 ± 27.5 vs. 112.6 ± 38.5 mg/dl, P = 0.56) showed no significant differences between both groups. No correlation was found between serum level of CETP and the characteristics of patients with RA including demographic data, disease activity markers (28-joint disease activity score, erythrocyte sedimentation rate, and C-reactive protein), serological markers (rheumatoid factor and anti-cyclic citrullinated peptide antibodies titer), as well as lipid profile parameters. On the contrary, serum level of CETP was significantly negatively correlated with CIMT (r=−0.321, P = 0.023). Conclusion Finally, we concluded that CETP was found to be low in patients with RA when compared with controls and is inversely related to CIMT, suggesting its possible role in cardiovascular mortality risk in this disease.